Penerapan Model Discovery Learning dalam Pembelajaran Fiqih - Fatin 'Arub (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2026)
The Discovery Learning model is a learning approach that emphasizes students’ active involvement in discovering concepts independently through processes of thinking, exploration, and reflection. This approach is particularly relevant in Fiqh learning, which requires not only the mastery of normative knowledge but also a deep understanding and conscious practice of Islamic legal principles. This study aims to analyze the implementation of Discovery Learning in Fiqh instruction and to examine its compatibility with Islamic educational principles based on Qur’anic evidence. This research employs a qualitative approach using the library research method, supported by theoretical analysis and naqli arguments, particularly Qur’anic verses that encourage reading, reasoning, and the use of intellect. The findings indicate that Discovery Learning enhances students’ activeness and understanding of Fiqh materials while fostering a deeper internalization of Islamic values. Furthermore, this approach has strong normative legitimacy within the Islamic educational framework, as it aligns with Qur’anic commands to seek knowledge actively and reflectively. Therefore, Discovery Learning can be considered a pedagogically relevant model for Fiqh learning that is fully consistent with Islamic values. Keywords: Discovery Learning, Fiqh Learning, Islamic Education, Qur’anic Foundations.